2010
DOI: 10.17305/bjbms.2010.2741
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Donor Age on Renal Graft Function in First Seven Post Transplant Days

Abstract: Increasing gap between demand and availability of human kidneys for transplantation has forced a re-evaluation of the limits on donor age acceptability. e present study included  patients who underwent kidney transplantation in University Clinical Centre Tuzla. In an observational cohort study we assessed impact of donor age on post transplant renal function by analyzing following parameters:  hour urine output, creatinine clearance (Cr Cl) and glomerular fi ltration rate (GFR). Depending on donor age reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…Results from previous studies, which have found that patients who receive kidneys from older donors carry a higher risk for graft failure, were not replicated in this study, which showed that grafts from older donors had a similar rate of survival as those from younger donors 22,23 …”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Results from previous studies, which have found that patients who receive kidneys from older donors carry a higher risk for graft failure, were not replicated in this study, which showed that grafts from older donors had a similar rate of survival as those from younger donors 22,23 …”
Section: Discussioncontrasting
confidence: 85%
“…Results from previous studies, which have found that patients who receive kidneys from older donors carry a higher risk for graft failure, were not replicated in this study, which showed that grafts from older donors had a similar rate of survival as those from younger donors. 22,23 This study found that a recipient weight between 10 and 20 kg was protective for graft survival. No past studies explicitly describe the effects of recipient weight on graft survival in pediatric recipients, possibly because it may be collinear with age.…”
Section: Discussionmentioning
confidence: 85%
“…Helanterä et al con rmed recently that donor age is an independent risk factor for DGF [31]. In contrast, Imamovic et al showed that donor age had no effect on allograft function in the rst seven days after transplantation [32]. Our results show that the donor age was negatively correlated with allograft function 30 days after transplantation.…”
Section: Discussionsupporting
confidence: 48%
“…Imamovic et al reported that the association between GFR, age, creatinine, and creatinine clearance was also statistically significant. Mean creatinine levels of patients transplanted from alive and deceased donor were compared (13). Although the results were not significant due to our limited number of patients (p>0.05), creatinine levels of patients transplanted from deceased donor were higher than the others.…”
Section: Koçyiğit Et Almentioning
confidence: 90%